"Hummingbird" floral traits interact synergistically to discourage visitation by bumble bee foragers. Issue 2 (9th January 2017) - Gegear, Robert J.; Burns, Rebecca; Swoboda‐Bhattarai, Katharine A.
Abstract: Pollination syndromes are suites of floral traits presumed to reflect adaptations to attract and utilize a "primary" type of animal pollinator. However, syndrome traits may also function to deter "secondary" flower visitors that reduce plant fitness through their foraging activities. Here we use the hummingbird‐pollinated plant species Mimulus cardinalis as a model to investigate the potential deterrent effects of classic bird syndrome traits on bumble bee foragers. To establish that M. cardinalis flowers elicit an avoidance response in bees, we assessed the choice behavior of individual foragers on a mixed experimental array of M. cardinalis and its bee‐pollinated sister species M. lewisii . As expected, bees showed a strong preference against M. cardinalis flowers (only 22% of total bee visits were to M. cardinalis ), but surprisingly also showed a high degree of individual specialization (95.2% of total plant transitions were between conspecifics). To determine M. cardinalis floral traits that discourage bee visitation, we then assessed foraging responses of individuals to M. cardinalis ‐like and M. lewisii ‐like floral models differing in color, orientation, reward, and combinations thereof. Across experiments, M. cardinalis ‐like trait combinations consistently produced a higher degree of flower avoidance behavior and individual specialization than expected based on bee responses to each trait in isolation. We then conducted a series of flower discrimination experiments to assess the ability of bees to utilize traits and trait combinations associated with each species. Relative to M. lewisii ‐like alternatives, M. cardinalis ‐like traits alone had a minimal effect on bee foraging proficiency but together increased the time bees spent searching for rewarding flowers from 1.49 to 2.65 s per visit. Collectively, our results show that M. cardinalis flowers impose foraging costs on bumble bees sufficient to discourage visitation and remarkably, generate such costs through synergistic color‐orientation and color‐reward trait interactions. Floral syndromes therefore represent complex adaptations to multiple pollinator groups, rather than simply the primary pollinator.